Code-Switching in Local Podcasts: A Study of Cinta Laura and Prilly Latuconsina on Puella - Qodriyati, Nurul Lailatul; Maharani, Ika Shakila; Pramesti, Rahmadini Windy; Yudhawati, Haliza Tri; Nargis (CV. Kalimasada Group Profesional, 2025)
This study examines code-switching patterns in Indonesian local podcasts, specifically focusing on the interactions between Cinta Laura and Prilly Latuconsina on Puella. Using a qualitative descriptive method, the research analyzes the types and functions of code-switching between Indonesian and English. The data collection involved observation and documentation of podcast episodes, with systematic transcription and analysis of code-switched utterances. The findings reveal that inter-sentential switching is the predominant type of code-switching used, with 32 instances identified - 13 switches from English to Indonesian and 19 switches from Indonesian to English. This research contributes to understanding how code-switching functions as a communication strategy in Indonesian digital media, particularly among bilingual public figures.